The Impact of Private Equity Investment on the New Quality Productivity of the Enterprises in Strategic Emerging Industry - Li Wang; Mu Zhang (Journal of Risk Analysis and Crisis Response (JRACR))
Private equity investment brings incremental funds to enterprises, but can it enhance the new quality productivity of enterprises and facilitate their high-quality development? From the perspective of technological innovation, this paper uses the relevant data of 378 listed companies in China’s strategic emerging industries from 2019 to 2023 to study the impact of private equity investment on the new quality productivity of strategic emerging industry enterprises, further examines the mediating role of technological innovation capability and the moderating role of regional science and technology finance levels, and investigates the heterogeneity of enterprise property rights nature, as well as industrial nature. The research results show that: First, private equity investment has a significant positive impact on the new quality productivity of enterprises in strategic emerging industries; Second, private equity investment can promote the development of new quality productivity of enterprises in strategic emerging industries by enhancing their technological innovation capability. Third, the level of regional science and technology finance positively moderate the promoting effect of private equity investment on the new quality productivity of enterprises in strategic emerging industries. Fourth, the new quality productivity of non-state-owned enterprises is more sensitive to private equity investment. The new quality productivity of enterprises in the new generation of information technology industry, new energy vehicle industry, new energy industry, energy conservation and environmental protection industry and digital creative industry is more sensitive to private equity investment. The research conclusion provides relevant inspirations for further utilizing private equity investment to enhance the new quality productivity of enterprises in strategic emerging industries.